2015
DOI: 10.3126/kumj.v11i4.12542
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Assessment of Partial Edentulous Patients Based on Kennedy’s Classification at Dhulikhel Hospital Kathmandu University Hospital

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
14
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 8 publications
10
14
0
5
Order By: Relevance
“…The study also, revealed a lack of awareness and needs to educate the population, which is in line with the results of the present study. In the examined population, the incidence of partial edentulism was 125 (62.5%) (Table2), which indicates that there was very highly significant difference in young female patients having been missing teeth, which is consistent with a study done by Sapkota b et al Who observed that females were more edentulous compared to males but at the same time, they show a higher level of replacement of missing teeth (Sapkota B et al 2013) [16]. This may be due to their dependency upon the males for their dental treatment to save the teeth.…”
Section: Discussionsupporting
confidence: 88%
“…The study also, revealed a lack of awareness and needs to educate the population, which is in line with the results of the present study. In the examined population, the incidence of partial edentulism was 125 (62.5%) (Table2), which indicates that there was very highly significant difference in young female patients having been missing teeth, which is consistent with a study done by Sapkota b et al Who observed that females were more edentulous compared to males but at the same time, they show a higher level of replacement of missing teeth (Sapkota B et al 2013) [16]. This may be due to their dependency upon the males for their dental treatment to save the teeth.…”
Section: Discussionsupporting
confidence: 88%
“…Partial edentulism and its patterns of occurrence have been studied in different countries in various selected populations by correlating between several parameters and the influencing factors such as socioeconomic status, educational status, age, and gender. [1,[4][5][6] There are studies which have analyzed the treatment needs and awareness regarding edentulousness in the screened populations. [4,5] Education is an important factor associated with the awareness of dental disease and its treatment needs.…”
Section: Discussionmentioning
confidence: 99%
“…This ultimately results in poor general health and also denies them the pleasure of taking food of their choice. [1] An edentulous space can be called a gap in the dental arch which could've been occupied by one or more teeth. It can be complete or partial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8, Issue, 4, pp. 16578-16580, April, 2017 16580 | P a g e the prevalence and awareness of tooth replacements among people [19].…”
Section: Discussionmentioning
confidence: 99%